Branched porphyrins as functional scaffolds for multisite bioconjugation. (22nd September 2014) - Engelen, Mireille; Lombardi, Angela; Vitale, Rosa; Lista, Liliana; Maglio, Ornella; Pavone, Vincenzo; Nastri, Flavia
Abstract Bioconjugation is a rapidly expanding field because of the numerous potential applications of bioconjugate materials. We explored the usefulness of branched porphyrins as rigid scaffolds, bearing multiple sites for bioconjugation. To this end, we first selected the tetrakis(p‐[aminomethyl] phenyl) porphyrin (TAMPP) macrocycle and developed a straightforward synthetic protocol, able to provide the desired tetraphenylporphyrin, carrying four functional amino groups. The partially protection of the amino groups by tert‐butoxy‐carbonyl allowed the selective and specific decoration of the porphyrin with different peptide sequences. To explore the utility of the macrocycle as molecular scaffold for bioconjugation, we selected peptide sequences able to function as thrombin inhibitors. In particular, two peptide sequences, named CS3 and ES7, able to interact, respectively, with the thrombin catalytic site and the fibrinogen recognition exosite, were joined onto the porphyrin macrocycle, providing the multisite‐directed inhibitor CS3–TAMPP–ES7. This multisite inhibitor and its MnIII complex are able to inhibit α‐thrombin‐catalyzed hydrolysis of Tos–Gly–Pro–Arg–nitroanilide with inhibition constants in the micromolar range, as well as the hydrolysis of the natural substrate fibrinogen. The inhibitor is resistant against enzymatic degradation by thrombin and is highly selective. The MnIII complex is capable of interacting with clot‐bound thrombin and partially inhibits clot growth in the presence of fibrinogen. The results herein reported are very promising, suggesting the potential of the newly developed conjugate as new imaging agents for clot detection.